(untitled) (Law, State and Telecommunications Review, 2019)
Purpose ”“ The article addresses the Brazilian participation in ICANN and the interests of Brazil. As an introduction to the topic, a synthesis is presented on the DNS system, as well as on the origins, nature and role of ICANN, its structure, functioning, principles and governance mechanisms. Then, the main criticisms by the doctrine regarding the (lack of) participation of peripheral countries in ICANN are summarized. The next topic lists the groups and support organizations that have Brazilian members and presents some concrete cases analyzed within the scope of ICANN that affect Brazilian interests, including the registration of new gTLDs. Methodology/approach/design ”“ The research has an eminently descriptive form, without neglecting the problematization of some related issues (specifically with regard to the interests of Brazil in ICANN). The theoretical framework is based on the studies of Milton Mueller and other authors (referred to in the bibliography) on internet governance. Findings ”“ The paper identifies and describes, in a succinct and objective way, the DNS system, ICANN (its origins, its role and its operation) and what are the Brazilian interests related to it. Originality ”“ It is a subject not yet explored in doctrine. Although there is a bibliography on the DNS, the origins, functioning, structure and especially the possible interests in Brazil in ICANN are little studied.